2014
DOI: 10.1177/1363460714524764
|View full text |Cite
|
Sign up to set email alerts
|

Imagining community: Visibility, bonding, and L Word audiences

Abstract: This essay examines the ways in which L Word audiences engaged with each other, and used the text as a way to build community and find acceptance in hetero-normative privileged society. This is particularly apparent among marginalized sexual minorities: bisexual, transgender, older lesbians, and lesbians of color. Viewers found connection through representations, shared narratives, and discourse. The resulting imagined communities provided cultural visibility and worked to make all sexual and gender identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…I referred earlier to conversations that I had had with other older women who were struggling to explain the intensity of their feelings about ‘Berena’; though the unfamiliar appearance on our screens of older wlw is obviously significant (see Kern, 2014 on the particular impact of ‘occasional visibility’), it is not a complete explanation. Many respondents talk about how much time they have devoted to ‘Berena’: ‘One problem is it is addictive and I can’t seem to quit!’; ‘In all honesty I follow the fandom a little too much to be healthy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…I referred earlier to conversations that I had had with other older women who were struggling to explain the intensity of their feelings about ‘Berena’; though the unfamiliar appearance on our screens of older wlw is obviously significant (see Kern, 2014 on the particular impact of ‘occasional visibility’), it is not a complete explanation. Many respondents talk about how much time they have devoted to ‘Berena’: ‘One problem is it is addictive and I can’t seem to quit!’; ‘In all honesty I follow the fandom a little too much to be healthy.…”
Section: Discussionmentioning
confidence: 99%
“…They describe not just the pleasure of watching two women exploring their sexuality, but the way that this has become a topic of conversation, or has facilitated sexual contact, with their partners. Kern (2014), too, speaks to women who enjoyed the American series The L Word as an ‘outlet’ for their same-sex desires within opposite-sex relationships.…”
Section: Coming Out: ‘I’m Not Sure If I Would Ever Have Had the Couramentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond Ireland, there is a considerable amount of research on the representation of LGBT sexuality on screen (Beirne, 2012;Dyer, 1990;Gross, 2001;Russo, 1981) as well as analyses of LGBT screen audiences (Dhoest, 2016;Kern, 2014). With the exception of a few key texts (Caldwell, 2008;Mayer, 2016;Moore, 2009), LGBT production of media has been less extensively researched and a focus on radio is even rarer.…”
Section: Irish Radio and Lgbt Identitymentioning
confidence: 99%
“…LGBTQ characters on screen tend to be qualitative and small scale. Existing studies have included straight-identified participants as well as LGBTQ-identified audience members and a range of gender identifications (Jackson and Gilberston, 2009;Kern, 2012;Kern, 2014; Dhaenens 2012). Kern (2012: 245) states that "[q]ueer media ethnographies are largely an unexplored area of research" and that existing studies tend to focus on gay male viewers, such as work by Miguel Malagreca (2007) andMark McClelland (2000).…”
Section: Audience Studies Of Women and Lesbian Audiencesmentioning
confidence: 99%